2019
DOI: 10.3390/ijms20020256
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Stresses Intervene with ABA Signaling to Induce Destructive Metabolic Pathways Leading to Death: Premature Leaf Senescence in Plants

Abstract: Abiotic stresses trigger premature leaf senescence by affecting some endogenous factors, which is an important limitation for plant growth and grain yield. Among these endogenous factors that regulate leaf senescence, abscisic acid (ABA) works as a link between the oxidase damage of cellular structure and signal molecules responding to abiotic stress during leaf senescence. Considering the importance of ABA, we collect the latest findings related to ABA biosynthesis, ABA signaling, and its inhibitory effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 158 publications
(217 reference statements)
2
61
0
Order By: Relevance
“…Abscisic acid (ABA) is a sesquiterpenoid and a signal molecule that is important in plant tolerance to stress factors . ABA can be synthesized by a direct pathway in fungi and by an indirect pathway in plants . In the indirect pathway, ABA is produced by oxidative cleavage of a C 40 carotenoid precursor .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abscisic acid (ABA) is a sesquiterpenoid and a signal molecule that is important in plant tolerance to stress factors . ABA can be synthesized by a direct pathway in fungi and by an indirect pathway in plants . In the indirect pathway, ABA is produced by oxidative cleavage of a C 40 carotenoid precursor .…”
Section: Introductionmentioning
confidence: 99%
“…11 ABA can be synthesized by a direct pathway in fungi and by an indirect pathway in plants. 12 In the indirect pathway, ABA is produced by oxidative cleavage of a C 40 carotenoid precursor. 11,13 Some endogenous enzymes, including aldehyde oxidase (AO), 9-cisepoxycarotenoid dioxygenase (NCED), and zeaxanthin epoxidase (ZEP), may be involved in the indirect pathway of ABA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of photosynthesis determines plant growth status, while chloroplast biogenesis and function affect the efficiency of photosynthesis. Recent studies have shown that photosynthesis is regulated by the target of rapamycin (TOR) and ABA signaling pathways [42,46,47]. TOR signaling acts as a positive regulatory factor to promote plant chloroplast biogenesis and photosynthesis, whereas ABA signaling acts as a negative regulatory signal to inhibit photosynthesis [42,[47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…ABA is an important messenger that acts as the signaling mediator during oxidation and stress adaption. ABA reduces ROS damage in two ways: by inhibiting ROS production during OXPHOS and by regulating the expression of genes related to ROS scavenging [39]. During OXPHOS, ABA binds to the receptor Mg-chelatase H subunit/putative ABA receptor (CHLH/ABAR) to induce TF PPR.…”
Section: Discussionmentioning
confidence: 99%